A água para o consumo humano: ensino por meio de temas com abordagem em ciência, tecnologia, sociedade e ambiente - RIBEIRO, Dayane Negrão Carvalho (Universidade Federal do Pará, 2017)
Water is a topic commonly treated in the teaching of science, but a resource availability scenario lacks discussions to training for citizenship through the recognition of scientific and technological issues surrounding access to the use and preservation of human life. In this scenario, this study sought to determine how the proposed theme "Water for Human Consumption" can influence the training for citizenship of elementary school students of a school of public schools in the city of Abaetetuba, generating in this context two thematic booklets on the proposal, namely: a thematic booklet for students and a booklet with activity suggestions for the teacher. The used theoretical foundation hás two sections. The first incorporates the approach in Science, Technology, Society and Environment and his notes to improve the teaching of science through teaching by theme based on three pedagogical moments of Delizoicov, Angotti and Pernambuco (2011), from the context of situations students in order to involve them actively in the search for solutions through diversified activities. In the second section I write about scientific knowledge related to water and its influence on the teaching of science. The research environment was formed through a short course, attended by eleven students of the sixth grade of elementary school as research subjects, as well as teacher-researcher. The action research was the methodological option chosen in this study to collect data, which are analyzed in light of the interpretative analysis of Creswell (2007). The data showed that the subject worked in the Science approach, Technology, Society and Environment enables students to recognize the problems of their reality, allowing its insertion in the search for solutions, and also shows the importance of working everyday reality, paying attention the difficulties of the students to express themselves orally and in writing. As for the teacher researcher, this study showed how reflective practice was important for the conduct of short course activities. Regarding the product of this work, the two primers for use in teaching-learning situation, I consider it possible that the treatment of the subject, because aroused the interest of students to continue the activities culminating in presentations to the school community. And yet, there was the drafting of a letter by students with proposals to solve specific problems that was sent to the school towards improving knowledge about the problems and possible solutions observed by students in their school environment, with regard to access to water for human consumption